Calibration of the muon barrel chambers for the EMMA experiment - Sorjonen, Jukka (2017)
The topic of this thesis was position calibration of muon barrel chambers used in the EMMA experiment. A detector ergo plank consist of seven chambers, and there were six uncalibrated detectors. The planks were set in a calibration stack, where there were four reference planks and six uncalibrated planks. Every chamber was divided into channels, and for every chamber, there was a specific position in the chamber. The position for each channel was ascertained by using manually calibrated reference planks and atmospheric muons. The calibration table was created for every chamber to obtain corresponding position for every channel in the chamber. The data collection was being done for approximately a month. There were 42 chambers in total to be calibrated, and it was possible to be created the calibration tables for 31 of them. The failed calibration originated from low statistic, probably due to broken chambers. There were some troublesome planks in the calibration stack, which have been through several calibrations. The experimental uncertainty was approximated by residual histograms. The residual histograms were done for reference planks, and for uncalibrated planks. When comparing the peak width and mean of these histograms, an information about the quality of the calibration was obtained.